Les promesses de la philosophie face aux attentes d’adolescents décrocheurs de lycée professionnel - Johanna Henrion-Latché (Éducation et Socialisation)
The project of teaching philosophy in the professional baccalaureate, has brought out of recent ministerial directives introducing optional philosophy workshops aimed at meeting ‘the adolescent’s needs’. But if half of the pupils who drop out of the education system come from professional high schools with an over-representation of teenagers from priority neighborhoods in the city, what needs are we talking about? Speak? Are adults able to engage with those who drop out? Our contribution aims to question adolescent vulnerabilities within so-called sensitive high schools located in QPV by the entry of the dropout population, we propose the results of an experiment based on the analysis of resignation letters written by adolescents to illustrate, by the language used, the adolescent questions and mobilizations, while situating the themes that are relevant during the philosophical dialogues.